Template-directed synthesis and characterization of microstructured ceramic Ce/ZrO2@SiO2 composite tubes - Schneider, Jörg J.; Naumann, Meike (Beilstein Journal of Nanotechnology, 2014)
An exo-templating synthesis process using polymeric fibers and inorganic sol particles deposited onto structured one-dimensional objects is presented. In particular, CeO2/ZrO2@SiO2 composite tubes were synthesized in a two-step procedure by using electrospun polystyrene fibers as fiber template. First, a sol–gel approach based on an exo-templating technique was employed to obtain polystyrene(PS)/SiO2 composite fibers. These composite fibers were subsequently covered by spray-coating with ceria and zirconia sol solutions. After drying and final calcination of the green body composites, the PS polymer template was removed, and composite tubes of the composition CeO2/ZrO2@SiO2 were obtained. The SiO2/ZrO2/CeO2 microtubes, which consist of interconnected silica particles, are held together by ceria and zirconia deposits formed during the thermal treatment process. These microtubes are mainly located in the pendentive connecting the individual spherical silica particles and glue them together. The composition and crystallinity of this material connecting the individual silica particles contains the elements Ce and Zr and O as mixed oxide solid solution identified by XRD, Raman and high-resolution TEM and EFTEM. High-resolution microscopy techniques allowed for an elemental mapping on the surface of the silica host structure and determination of the O, Zr and Ce elemental distribution with nm precision.
Keywords: electrospinning; exotemplating; nanostructured solid solution; sol–gel chemistry; Stoeber process; ternary oxide

(untitled) - Kiss, S. J.; Zec, S.; Boskovic, S. (J. Alloys Compd., 1999)

(untitled) - Reddy, B. M.; Saikia, P.; Bharali, P.; Katta, L.; Thrimurthulu, G. (Catal. Today, 2009)

(untitled) - Reddy, B. M.; Lakshmanan, P.; Bharali, P.; Saikia, P. (J. Mol. Catal. A: Chem., 2006)

(untitled) - Raju, V.; Jaenicke, S.; Chuah, G.-K. (Appl. Catal., B: Environ., 2009)

(untitled) - Fornasiero, P.; Balducci, G.; Di Monte, R.; Kaspar, J.; Sergo, V.; Gubitosa, G.; Ferrero, A.; Grazianti, M. (J. Catal., 1996)

(untitled) - Devaraju, M. K.; Liu, X.; Yusuke, K.; Yin, S.; Sato, T. (Nanotechnology, 2009)

(untitled) - Bernal, S.; Calvino, J. J.; Gatica, M. A.; Larese, C.; Perez Omil, J. A.; Pintado, J. M. (Catal. Today, 1999)

(untitled) - Lin, J.-D.; Duh, J.-G. (J. Am. Ceram. Soc., 1998)

(untitled) - Yuan, Q.; Liu, Q.; Song, W.-G.; Feng, W.; Pu, W.-L.; Sun, L.-D.; Zhang, Y.-W.; Yan, C.-H. (J. Am. Chem. Soc., 2007)

(untitled) - Shevchenko, V. Y.; Glushkova, V. B.; Panova, T. I.; Podzorova, L. I.; Ilicheva, A. A.; Lapshin, A. E. (Inorg. Mater., 2001)

(untitled) - Luo, X.; Zhu, B.; Xia, C.; Niklasson, G. A.; Granqvist, C. G. (Sol. Energy Mater. Sol. Cells, 1998)

(untitled) - Reddy, B. M.; Thrimurthulu, G.; Saikia, P.; Bharali, P. (J. Mol. Catal. A: Chem., 2007)

(untitled) - Masui, T.; Peng, Y.; Machida, K.-I.; Adachi, G.-Y. (Chem. Mater., 1998)

(untitled) - Crepaldi, E. L.; de A. A. Soler-Illia, G. J.; Bouchara, A.; Grosso, D.; Durand, D.; Sanchez, C. (Angew. Chem., Int. Ed., 2003)

(untitled) - Nozawa, T.; Sato, S.; Takahashi, R. (Top. Catal., 2009)

(untitled) - Greiner, A.; Wendorff, J. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Glushkova, V. B. (Grebenshchikov Inst. of Silicate Chemistry ,USSR Acad. Sci., 1972)

(untitled) - Garvie, R. C. (J. Phys. Chem., 1965)

(untitled) - Krauth, F.; Meyer, H. (Ber. Dtsch. Keram. Ges., 1965)

(untitled) - Lopez, E. F.; Escribano, V. S.; Panizza, M.; Carnascialli, M. M.; Busca, G. (J. Mater. Chem., 2001)

(untitled) - Mc Bride, J. R.; Hass, K. C.; Poindexter, B. D.; Weber, W. H. (J. Appl. Phys., 1994)

(untitled) - Ziegler, A.; Kisielowski, C.; Hoffmann, M. J.; Ritchie, R. O. (MRS Proceedings, 2002)